Permanence of CDM forests or non-permanence of land use related carbon credits? - Michael Dutschke (Hamburg Institute of International Economics (HWWA), 2001)
Carbon sequestration projects in the context of the Clean Development Mechanism (CDM) suffer from the stigma of permanence risk. The risk that carbon reduced or sequestered in forestry projects is release further down the road is in fact undeniable, whoever bears the onus. The merit of the so-called ?ton/year approach? is to destroy the fiction of infinity when talking about permanent sequestration. The merit of the ?Columbian proposal? is to destroy the fiction of comparability between technological emission reduction and sequestration in natural systems. Yet, both approaches are discussed as more or less unrelated alternatives. By making use of both methodologies and providing a link between both proposals on permanence in CDM forestry, the present article puts forward the proposal of leasing reduction certificates. – – Kohlenstoffbindungsprojekte im Rahmen des Kompensationsmechanismus für Saubere Entwicklung (Clean Development Mechanism - CDM) des Kyoto-Protokolls leiden unter dem Stigma des Permanenzrisikos. Das Risiko, dass die in Waldprojekten erreichte Bindungs- oder Reduzierungseffekte durch spätere Entwaldung wieder zunichte gemacht werden, ist nicht von der Hand zu weisen, einerlei, wer es zu tragen hat. Das Verdienst des sog. ?ton/year approach? ist, die Fiktion der Unendlichkeit in Bezug auf Bindungspermanenz zerstört zu haben. Demgegenüber steht der sog. ?kolumbianische Vorschlag?, der die Fiktion der Vergleichbarkeit zwischen technischerEmissionsreduzierung und natürlicher Kohlenstoffbindung zerstört. Beide Ansätze stehen derzeit unverbunden im Raum. Der vorliegende Artikel macht sich der Methodik beider Vorschläge zunutze und schlägt die Verbindung zwischen ihnen. Er resultiert im Vorschlag, des Leasings von Reduktionszertifikaten.
Keywords: 330; Klimaschutz; Kohlendioxid; Aufforstung; Wald; Internationale Umweltpolitik; Umweltzertifikat; Welt